Quality assessment of ozone-treated citrus fruit juices - Abdul Karim Shah, Nor Nadiah; Sulaiman, Alifdalino; Sidek, N. S. M.; Supian, N. A. M. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
The aim of the present work was to analyse the impact of ozone treatment on the physicochemical parameters and antioxidant capacity of citrus fruit juices (orange, lemon and lime) with different juice components (total soluble solids). Each sample was ozonated at different ozone treatment time, between 0 to 30 min with fixed ozone concentration of 600 mg/h. The synergistic effects of ozone treatment and the different types of juice were found to significantly affect the pH, total colour difference (TCD), pectin methylesterase (PME) activity, ascorbic acid (AA) and total phenolic content (TPC) of treated juices, while total soluble solids, turbidity and 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay were found to be unchanged. It was observed that PME activity decreased with treatment time and this is related to the decrease of juice turbidity (R2 = 0.86) and TCD (R2 = 0.78). Ascorbic acid showed an abrupt decrease in all the juices especially in orange juice with percentage loss of 85%. TPC also showed decreasing trend for all juices with maximum loss of 84.4% in lemon juice after 30 min of ozonation time. The present work also found that lemon juice could retain most of its antioxidant activities (DPPH 98.9%, TPC 96%, AA 86.7%) after 10 min of ozone treatment time in comparison to orange and lime juices.